Aristotle on false reasoning : language and the world in the Sophistical refutations - Schreiber, Scott G. (Scott Gregory), 1952- (SUNY series in ancient Greek philosophy., 2003)
"Presenting the first book-length study in English of Aristotle's Sophistical Refutations, this work takes a fresh look at this seminal text on false reasoning. Through a careful and critical analysis of Aristotle's examples of sophistical reasoning, Scott G. Schreiber explores Aristotle's rationale for his taxonomy of twelve fallacy types. Contrary to certain modern attempts to reduce all fallacious reasoning to either errors of logical form of linguistic imprecision, Aristotle insists that, as important as form and language are, certain types of false reasoning derive their persuasiveness from mistaken beliefs about the nature of language and the nature of the world."--Jacket